PENGUATAN PRODUK REKOMENDASI PADA PERMENKUMHAM NOMOR 2 TAHUN 2019 TENTANG PENYELESAIAN DISHARMONI PERATURAN PERUNDANG-UNDANGAN MELALUI MEDIASI - Abidin, Handa S (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2020)
The recommendations under the Minister of Law and Human Rights of the Republic of Indonesia Regulation Number 2 Year 2019 concerning the Settlement of Disharmonisation of Laws and Regulations Through Mediation (hereafter: MLHR Number 2 Year 2019) need to be strengthened. This strengthening is important because if the recommendations in MLHR Number 2 Year 2019 are ignored by the recipients of recommendations, the essence and the existence of MLHR Number 2 Year 2019 will not be optimally used for the harmonisation of laws and regulations in Indonesia. This research offered suggestions regarding the strengthening of the recommendations that focused on: the goodwill of the recipients of recommendations, content of recommendations, procedures after recommendations have been issued, online access, and time certainty. The implementation of these suggestions can play an important role in strengthening not only for the implementation of the recommendations by the recipients of recommendations, but also if the recommendations are decided not to be implemented by the recipients of recommendations. The option of implementing or not implementing the recommendations by the pertinent recipients of recommendations must provide responsibility to all parties that are involved and also to the public in accordance with the spirit of Law of the Republic of Indonesia Number 14 Year 2008 concerning the Openness of Public Information.